2018
DOI: 10.1039/c8ra00922h
|View full text |Cite
|
Sign up to set email alerts
|

Dispersible MoS2 micro-sheets induced a proinflammatory response and apoptosis in the gills and liver of adult zebrafish

Abstract: Molybdenum disulfide (MoS 2 ), one of the next-generation two-dimensional materials (2DMs), has attracted increasing attention due to its unique physicochemical properties. However, the aquatic toxicity of dispersible MoS 2 is still unknown. Herein, we synthesized chitosan functionalized MoS 2 (CS-MoS 2 ) micro-sheets with a satisfying water-dispersible performance. The average length and width of the asprepared CS-MoS 2 micro-sheets were 5.04 mm and 3.12 mm, respectively, and they had a pristine 2H polymorph.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…Yu et al demonstrated that chitosan functionalized MSNs induced ROS accumulation in human dermal cells 37 and in the gills and liver of adult zebrafish. 38 Consistently, Pardo et al 39 found that fullerene-like MSNs could induce robust protective antioxidant/detoxification defenses in human bronchial cells, indicating ROS generation in this cell line. Using E. coli as the model organism, Wu et al 40 and Qureshi et al 41 proved that the MSN exposure at a concentration of 100-1000 μg/mL dramatically increased the intracellular concentrations of ROS in bacteria.…”
Section: Ros-induced Cytoskeleton Arrangement Participates In the Impmentioning
confidence: 77%
“…Yu et al demonstrated that chitosan functionalized MSNs induced ROS accumulation in human dermal cells 37 and in the gills and liver of adult zebrafish. 38 Consistently, Pardo et al 39 found that fullerene-like MSNs could induce robust protective antioxidant/detoxification defenses in human bronchial cells, indicating ROS generation in this cell line. Using E. coli as the model organism, Wu et al 40 and Qureshi et al 41 proved that the MSN exposure at a concentration of 100-1000 μg/mL dramatically increased the intracellular concentrations of ROS in bacteria.…”
Section: Ros-induced Cytoskeleton Arrangement Participates In the Impmentioning
confidence: 77%
“…[ 93 ] Furthermore, Yu et al have demonstrated the induction of pro‐inflammatory and apoptotic responses (e.g., IL‐1β, IL‐6, and AIF gene) in the livers of adult zebrafish by chitosan‐functionalized MoS 2 micro‐sheets. [ 150 ] Thus, much attention should be paid to the adverse effects induced by MoS 2 NMs for developing safer nanoapplications.…”
Section: Cell Type‐specific Responses and Molecular Mechanismsmentioning
confidence: 99%
“…[30,66] However, despite these concerns there is currently no direct evidence for MoS 2 -induced hepatotoxicity except the documentation of pro-inflammatory effects (e.g., IL-1β, IL-6, and AIF gene) and occurrence of apoptosis in the liver tissue of zebrafish. [27] Additional experimentation in rodents is required for the further assessment of MoS 2 safety in vivo.…”
Section: Cations For Example Moomentioning
confidence: 99%
“…[25,26] For instance, Yu et al have demonstrated the development of localized liver lesions in adult zebrafish during exposure to dispersible MoS 2 micro-sheets. [27] However, the mechanism of liver toxicity at the molecular level is still unclear and there has been no attempt to differentiate between the adverse impact on specific liver cell types. This stresses the importance of understanding the differential effects of BN or MoS 2 on specific liver cell types that may encounter the 2D materials that are being delivered to liver sinusoids from hepatic and portal blood circulations.…”
Section: Introductionmentioning
confidence: 99%